The Influence of Customer Trust, Customer Satisfaction and Institutional Image on Customer Loyalty at BMT Istiqlal Pekalongan - Fikky Aryudha; Nur Kholidah (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to examine the effect of customer trust, customer satisfaction, and institutional image on customer loyalty at BMT Istiqlal Pekalongan. The research addresses a gap in previous studies, which have rarely examined these variables simultaneously within the context of Islamic microfinance institutions. A quantitative explanatory researcch design was employed to analyze the causal relationships among variables. The study involved 100 active customers selected through purposive sampling. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4. The measurement model evaluation confirmed that all indicators met the criteria for convergent validity and reliability. The structural model results indicate that customer trust, customer satisfaction, and institutional image have positive and significant effects on customer loyalty. Customer trust emerged as the most dominant variable influencing loyalty, followed by customer satisfaction and institutional image. The coefficient of determination (R² = 0.516) shows that the three independent variables explain 51.6% of the variance in customer loyalty. These findings highlight the importance of strengthening trust-based relationships, enhancing service quality, and maintaining a positive institutional image to foster sustainable customer loyalty in Islamic microfinance institutions.